Evaluation of aphasia between the traditional point of view and that of mediation - BADAOUI, FOUZIA (Journal of Social Sciences and Humanities, 2020)
The aim of this study is to establish an analysis of the methods applied in the diagnosis, evaluation and prognosis of aphasia from the traditional point of view to the point of view of the theory of mediation. By diagnosis, we mean the procedure followed in detecting disorder observed from the symptoms or manifestations of the disorder appearing on the subject. The prognosis is the description of the risks of evolution (positive or negative) of the observed disorder. For its part, rehabilitation is the therapeutic management of the disorder observed from a protocol that allows the therapist to recover the language functions (in our context) reached. Using these three types of analysis, we will discuss how traditional methods and the method of mediation theory proceed in the study of language disorders or cognition. In this context, we have read three texts whose content relates to the assessment of aphasia, its diagnosis and rehabilitation. We derive from this analysis the approach of traditional methods in the diagnosis, evaluation and prognosis of aphasia by comparing it to the clinical method of mediation theory. Through a comparative approach, we have demonstrated how traditional methods evaluate aphasia and other language disorders, and how the therapeutic protocol is done. We have then presented the clinical method of the theory of mediation and its procedure in the diagnosis and rehabilitation of this type of disorders. We will highlight how the model of mediation differs from empirical methods and its contribution in the analysis of language in general, and aphasia in particular. We have finished this study by showing the contribution of the clinical method of mediation in the diagnosis, or the therapeutic management of language disorders